Merchandise Ownership and Social Stratification: A Study of Taylor Swift Fandom in Indonesia - Nawang Wulan; Desideria Dwihadiah (Program Studi Ilmu Komunikasi Universitas Serang Raya, 2026)
This research examines how merchandise ownership can create social stratification among Taylor Swift fans (Swifties) in Indonesia. Using a qualitative approach with a critical paradigm, primary data were collected through in-depth interviews with six purposively sampled Indonesian Swifties representing variations in merchandise ownership. Secondary data came from digital observation of a fan’s account identified by informants as an influencer and a community’s WhatsApp Group’s transcript. Analysis utilized Miles & Huberman’s (1994) interactive model within the theoretical frameworks of Illouz’s (2007; 2018) Emotional Capitalism, as well as Bourdieu’s (1984; 1986) Distinction and Cultural Capital. Findings reveal that social stratification in Swifties Indonesia’s community is driven by emotional capitalism, making consumption feels unlike economic transactions. As a result, merchandise becomes cultural capital, consumed unevenly due to disparities in economic power and constraints on structural distribution. That inequality is used as a means of differentiation, leading to stratification. Rooted in false consciousness, this hierarchy resists change. Therefore, researcher propose that fans break free from false consciousness, community becomes more introspective, and the entertainment industry becomes more inclusive to transcend from a hierarchy framed as love. Future research suggestions include international comparisons, extending the research period, and focusing on peripheral perspectives.